The community rule 1QS, 1QSa and 1QSb a philological commentary. - MURAOKA. TAKAMITSU (PEETERS PUBLISHERS, 2022)
Among the Dead Sea Scrolls The Community Rule (1QS) occupies a very important position. Written in Hebrew and being one of the seven documents found in the late forties of the 20th century it has attracted much attention from a host of scholars. It is not a biblical manuscript, but a document written sometime in the second century B.C.E. in Palestine, and has been read and studied in the Qumran community as we can conclude that as many as ten fragments of the document were subsequently unearthed in another Qumran cave. Because of its contents the document was sometimes called the constitution of the community. The document also throws much light on aspects of the post-biblical Hebrew. Its Hebrew, certainly reflecting Biblical Hebrew, is not merely an imitation of it.0In addition, two much shorter documents, though not part of 1QS, but affiliated with it in their contents, have been included: Rule of the Congregation (1QSa) and Rule of Benedictions (1QSb).0This monograph presents the entire text, largely based on a recent edition of Prof. Qimron (2020), accompanied by an English translation of our own and a linguistic and text-critical commentary. Studies published in Modern Hebrew have been consulted.